Jamur Makro Ascomycota di TWA Suranadi Lombok Barat - Meilinda Pahriana Sulastri; Hasan Basri (Fakultas MIPA UNM, 2020)
Abstract. Fungal species from the Ascomycota have a very important role, especially in their function as decomposers in the forest ecosystem. This study aims to identify the Ascomycota macrofungi found in TWA Suranadi. This is a descriptive exploratory study using the cruise method. Identification is done by matching the morphological characters with reference books and various scientific journals on macrofungi. Based on the results of the study, 3 species from Xylaria sp.1, Xylaria sp. 2 and Peziza sp.Keywords. fungi, Ascomycota, TWA Suranadi